Viscosities and densities of binary and ternary blends of palm oil plus palm biodiesel plus diesel fuel at different temperatures - Baroutian, S.; Aroua, M.K.; Abdul Raman, Abdul Aziz; Sulaiman, N.M.N. (American Chemical Society, 2010)
Vegetable oil-based fuels are promising alternative fuels for diesel engines because of their environmental and strategic advantages. In this work, binary and ternary blends of palm oil, biodiesel, and diesel fuel were prepared, and dynamic viscosities and densities of blends were measured as functions of temperature. The binary and tertiary blends demonstrate a temperature-dependent behavior, and viscosities and densities decreased nonlinearly and linearly with temperature, respectively. The evaluation of the measured viscosities of binary and tertiary blends was completed, and the hest correlation was obtained by a polynomial regression.